Identifying copulative in Zulu and Southern Sotho - Posthumus, L. C. (South African Journal of African Languages, 1988)
Comparing language data from Zulu and Southern Sotho leads to the postulation of a uniform syntactic diachronic structure for the identificative copulative word group. Although the two languages seem to be completely different in their formation of identifying copulatives, the contrary is true. Neither of these two languages reflects the true nature of this copulative construction when studied individually. A comparative investigation reveals the presence of an (underlying) copulative verb stem (*-li/-le in the positive and -si/-se in the negative of the two languages respectively) in all forms of the non-inchoative copulative verb groups. This comparison suggests further that the copula of the copulative of identification in Zulu is ngi and not nga or ng- or ngu as generally accepted.